Adherence to the Healthy Eating Index-2015 and Other Dietary Patterns May Reduce Risk of Cardiovascular Disease, Cardiovascular Mortality, and All-Cause Mortality - Hu, Emily A; Steffen, Lyn M; Coresh, Josef; Appel, Lawrence J; Rebholz, Casey M (The Journal of nutrition, 2020)
The Healthy Eating Index-2015 (HEI-2015) score measures adherence to recommendations from the 2015-2020 Dietary Guidelines for Americans. The HEI-2015 was altered from the HEI-2010 by reclassifying sources of dietary protein and replacing the empty calories component with 2 new components: saturated fats and added sugars. Our aim was to assess whether the HEI-2015 score, along with 3 other previously defined indices, were associated with incident cardiovascular disease (CVD), CVD mortality, and all-cause mortality. We conducted a prospective analysis of 12,413 participants aged 45-64 y (56% women) from the Atherosclerosis Risk in Communities (ARIC) Study. The HEI-2015, Alternative Healthy Eating Index-2010 (AHEI-2010), alternate Mediterranean (aMed) diet, and Dietary Approaches to Stop Hypertension Trial (DASH) scores were computed using the average dietary intakes of Visits 1 (1987-1989) and 3 (1993-1995). Incident CVD, CVD mortality, and all-cause mortality data were ascertained from baseline through 31 December, 2017. We used Cox proportional hazards models to estimate HRs and 95% CIs. There were 4509 cases of incident CVD, 1722 cases of CVD mortality, and 5747 cases of all-cause mortality over a median of 24-25 y of follow-up. Compared with participants in the lowest quintile of HEI-2015, participants in the highest quintile had a 16% lower risk of incident CVD (HR: 0.84; 95% CI: 0.76-0.93; P-trend < 0.001), 32% lower risk of CVD mortality (HR: 0.68; 95% CI: 0.58-0.80; P-trend < 0.001), and 18% lower risk of all-cause mortality (HR: 0.82; 95% CI: 0.75-0.89; P-trend < 0.001) after adjusting for demographic and lifestyle covariates. There were similar protective associations for AHEI-2010, aMed, and DASH scores, and no significant interactions by race. Higher adherence to the 2015-2020 Dietary Guidelines for Americans was associated with lower risks of incident CVD, CVD mortality, and all-cause mortality among US adults.